Oblique-Angle Deposited SiO2/Al Omnidirectional Reflector for Enhancing the Performance of AlGaN-Based Ultraviolet Light-Emitting Diode. (10th February 2020) - Lee, Jeongwon; Seong, Tae-Yeon; Amano, Hiroshi
Abstract : We report the improvement of the performance of AlGaN-based ultraviolet (UV)-light-emitting diodes (LEDs) using oblique-angle deposited SiO2 -based omnidirectional reflectors (ODRs). The electron-beam (e-beam) deposition at angles of 60° and 80° resulted in the formation of porous SiO2 films. The refractive index ( n ) varied from 1.49 to 1.25 at 365 nm with changing angle from 0 to 80°. Simulation based on the transfer matrix method showed that the porous SiO2 ( n = 1.25)/Al ODR gave the normal incidence reflectance of 95.4% at 365 nm, whereas the conventional SiO2 ( n = 1.49)/Al and ITO/Al reflectors have the normal incidence reflectance of 93.8% and 79%, respectively. The UV-LED with different reflectors had a forward voltage in the range of 3.40–3.51 V at 20 mA. The UV-LEDs with porous SiO2 /Al ODRs (40% mesh ohmic area) yielded 21% higher light output at 100 mA and 24% relative external quantum efficiency (EQE) at 6 mA compared with the one with a reference ITO/Al reflector. The plan-view emission images showed that the SiO2 /Al ODR UV-LED displayed better current spreading than the reference one with the ITO/Al reflector experiencing current crowding near the p -pad.